Beyond Vessel Diameters: Non-invasive Monitoring of Flow Patterns and Immune Cell Recruitment in Murine Abdominal Aortic Disorders by Multiparametric MRI - Temme, Sebastian; Yakoub, Mina; Bouvain, Pascal; Yang, Guang; Schrader, Jürgen; Stegbauer, Johannes; Flögel, Ulrich (Frontiers in Cardiovascular Medicine, 2021)
The pathophysiology of the initiation and progression of abdominal aortic aneurysms (AAA) and aortic dissections (AAD) is still unclear. However, there is strong evidence that monocytes and macrophages are of crucial importance in these processes. Here, we utilized a molecular imaging approach based on background-free 19F MRI and employed perfluorocarbon nanoemulsions (PFCs) for in situ 19F labeling of monocytes/macrophages to monitor vascular inflammation and AAA/AAD-formation in angio¬tensin II (angII)-treated apolipoproteinE-deficient (apoE-/-) mice. In parallel, we used conventional 1H MRI for the characterization of aortic flow patterns and morphology. AngII (1 µg/kg/min) was infused into apoE-/- mice via osmotic minipumps for ten days and mice were monitored by multiparametric 1H/19F MRI. PFCs were intravenously injected directly after pump implantation followed by additional applications on day two and four to allow an efficient 19F loading of circulating monocytes. The combination of angiographic, hemodynamic, and anatomical measurements allowed an unequivocal classification of mice in groups with developing AAAs, AADs or without any obvious aortic vessel alterations despite the exposure to angII. Maximal luminal and external diameters of the aorta were enlarged in AAAs, whereas AADs showed either a slight decrease of the luminal diameter or no alteration. 1H/19F MRI after intravenous PFC application demonstrated significantly higher 19F signals in aortae of mice that developed AAAs or AADs as compared to mice in which no aortic disorders were detected. High resolution 1H/19F MRI of excised aortae revealed a patchy pattern of the 19F signals predominantly in the adventitia of the aorta. Histological analysis confirmed the presence of macrophages in this area and flow cytometry revealed higher numbers of immune cells in aortae of mice that have developed AAA/AAD. Importantly, there was a linear correlation of the 19F signal with the total number of infiltrated macrophages. In conclusion, our approach enables a precise differentiation between AAA and AAD as well as visualization and quantitative assessment of inflammatory active vascular lesions, and therefore may help to unravel the complex interplay between macrophage accumulation, vascular inflammation, and the development and progression of AAAs and AADs.